Unveiling the truth: greenwashing in sustainable finance - Dempere, Juan; Alamash, Ebrahim; Mattos, Paulo (Frontiers in Sustainability, 2024)
Introduction: Greenwashing in sustainable finance involves misleading portrayals of investment products as environmentally friendly. This study explores the prevalence of greenwashing, its forms, impacts, and potential remedies. It underscores the need to align investor values with genuine environmental sustainability, emphasizing the pitfalls of greenwashing in sustainable finance. Methods: The study employs a scoping review methodology guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. It involves systematically searching, selecting, and synthesizing evidence from various databases and sources to map critical concepts, types of evidence, and research gaps in greenwashing within sustainable finance. Results: The study reveals diverse greenwashing strategies across industries, including ambiguous language, irrelevant claims, and opacity. It highlights greenwashing’s severe consequences on corporate reputation, financial performance, and stakeholder trust. The effectiveness of regulatory bodies, Non-Governmental Organizations, and certifications in curbing greenwashing is discussed, though their effectiveness is debatable. The research also examines greenwashing’s impact on investor behavior and decision-making. Discussion: This research contributes to understanding greenwashing in sustainable finance, emphasizing vigilance, transparency, and accountability. It calls for more stringent regulations, international cooperation, and public awareness to combat greenwashing effectively. The study also suggests that businesses should adopt genuine and transparent environmental practices to avoid the risks of greenwashing, including legal repercussions. For future research, the study proposes a deeper exploration of the mechanisms enabling greenwashing and the effectiveness of different regulatory strategies and measures to combat it.